High-Voltage Monolithic Active Pixel Sensors Based Tracker for the Mu3e Experiment - Shrestha, Shruti (Journal of Nepal Physical Society, 2024)
The Mu3e experiment is searching for the decay µ + → e+ e− e+ , which involves a violation of charged lepton flavor. The goal is to achieve a branching fraction sensitivity of four orders of magnitude higher than existing limits. To accurately measure the momentum and vertex position of low momentum electrons (10-53 MeV/c) produced by this rare decay, a tracking detector made from High-Voltage Monolithic Active Pixel Sensors (HV-MAPS) has been used. The MuPix7 chip has an HV- MAPS architecture and is manufactured using 180 nm High Voltage CMOS (HV-CMOS) technology. HV-MAPS are preferred due to their ability to be thinned to 50 µm, tolerance to radiation, high time resolution, and cost-effectiveness. Additionally, to minimize the material used, the pixel readout electronics are embedded inside the sensor chip, supported by a low-mass mechanical structure built with 25 µm Kapton foil. The MuPix7 chip is the first HV-MAPS prototype that implements all functionalities of the final sensor, including a readout state machine. Based on a high-rate test beam, the it has a particle detection efficiency of 99% and meets all the requirements for a small-scale prototype.